Metodologia para Cálculo/Análise do Espectro Raman de Sistemas RNA/DNA em Meio Aquoso Baseada na Teoria do Funcional da Densidade - Oliveira, Micael Estevão Pereira de (2023)
Vibrational spectroscopy (Raman and infrared, the latter less suitable for systems in aqueous solution), a tool widely used in chemistry and physics for the characterization of molecular systems, is capable of carrying out assignments of the normal modes of atomic vibrations to their lengths wave (or frequencies) when the number of atoms is large, which is the case of RNA/DNA systems of biological interest. In this qualification, we developed a methodology (based on the use of the Density Functional Theory - DFT) to calculate/characterize the Raman spectra of RNA/DNA systems in aqueous systems, initially in the context of the Continuous Polarizable Model (PCM). At the zero level of the methodology (the simplest), we consider that the Raman of the system strongly depends on the vibrational properties of the individual bases, taking into account the sequence of the bases and the percentage of each one in the RNA/DNA system to obtain its Raman spectrum and making assignments of their vibrational modes from those individual bases - are not taken into account as inevitably between bases nor the existence of sugars and monophosphates. However, two other levels will be carried out for future results, they are: level one, which establishes that the Raman of the system depends on the vibrational properties of the bases + sugars (ribose or deoxyribose) + monophosphate group, that is, individual nucleotides – without considering so comfortable among such; level two, where it was conceptualized that the Raman of the RNA/DNA system also depends on the vibrational properties arising from the happy moments between the nucleotides themselves (64 codons, in the case of mRNA), thus evaluating a more complete molecular set. In addition, the direct influence of Explicit Waters (close to the base sequences) + PCM will be followed, in order to observe the difference in approximation of DFT peaks with experimental ones. To validate the methodology, we present here: (a) calculating DFT in the PCM model (aqueous medium) and Raman measurements of the vibrational properties of the RNA/DNA bases, as well as their assignments; (b) Molecular Dynamics calculations, in order to evaluate the translations explicitly; (c) zero-level calculations on vibrational data published in the literature, having obtained a good level of agreement between theoretical (PCM) and experimental wavelengths, as in the case of microRNA-16 associated with cancer, whose sequence is UAGCAGCACGUAAAUAUUGCGCG.